Targeting Cytochrome P450 1A1 Enzyme with Crucifer Phytocomponents: An In Silico Approach for Chemopreventive Drug Design against Lung Cancer - Inbathamizh, L. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Metabolism of carcinogens plays a key role in cancer. Cytochrome P450, family 1, subfamily A, polypeptide 1 (CYP1A1) is one of the main cytochrome P450 enzymes. It is involved in the activation of compounds such as polycyclic aromatic hydrocarbons with carcinogenic properties associated with lung cancer. Inhibition of enzymes that activate carcinogenesis is a major strategy of chemoprevention. Thus, CYP1A1 is selected as the target protein. Crucifer vegetables offer a promising source of phytochemicals that are emerging as strong contenders in the arena of cancer chemoprevention and thus can be analyzed as ligands to the selected target. Aim: The study is an attempt to find an in silico solution to lung cancer by CYP1A1 inhibition-based chemoprevention using crucifer phytocomponents. Materials and Methods: Bioinformatics databases and tools are used. The study involves the structural analysis of CYP1A1 and its interaction with crucifer ligands using Modeller 9V2 and AutoDock, respectively, as the prominent software. Pharmacokinetic properties of the ligands are also predicted with ACD/I-Lab 2.0 modules. Results: The findings indicated effective active site interactions of CYP1A1 with the crucifer phytocomponents. Glucosinolate was found to be the best inhibitory ligand with docking energy âˆ’16 KJ/mol and 9 hydrogen bonds. The compounds also exhibited preferable drug properties. Indole-3-carbinol and 3, 3â€™-Diindolylmethane seemed to possess more druglikeness comparatively. Conclusion: From the study, it can be concluded that crucifer phytocomponents can act as natural, safe, and potent drug candidates in anti-lung cancer drug design.